PAAR proteins act as the ‘sorting hat’ of the type VI secretion system - Wood,TE; Howard,SA; Wettstadt,S; Filloux,A (Microbiology, 2019)
Bacteria exist in polymicrobial environments and compete to prevail in a niche. The type VI secretion system (T6SS) is a nanomachine employed by Gram-negative bacteria to deliver effector proteins into target cells. Consequently, T6SS-positive bacteria produce a wealth of antibacterial effector proteins to promote their survival among a prokaryotic community. These toxins are loaded onto the VgrG–PAAR spike and Hcp tube of the T6SS apparatus and recent work has started to document the specificity of effectors for certain spike components. Pseudomonas aeruginosa encodes several PAAR proteins, whose roles have been poorly investigated. Here we describe a phospholipase family antibacterial effector immunity pair from Pseudomonas aeruginosa and demonstrate that a specific PAAR protein is necessary for the delivery of the effector and its cognate VgrG. Furthermore, the PAAR protein appears to restrict the delivery of other phospholipase effectors that utilise distinct VgrG proteins. We provide further evidence for competition for PAAR protein recruitment to the T6SS apparatus, which determines the identities of the delivered effectors.